2020
DOI: 10.1097/md.0000000000020886
|View full text |Cite
|
Sign up to set email alerts
|

The inferior parathyroid glands preserved in site recover faster than the superior parathyroid glands preserved in site after thyroid surgery for carcinoma

Abstract: Due to the great difficulty in being preserved in site for the variable positions, the inferior parathyroid glands were advised to being routinely autotransplanted to prevent permanent hypoparathyroidism. The aim of this study was to compare the performance in the function of the superior parathyroid glands preserved in site with that of the inferior parathyroid glands preserved in site. We conducted a retrospective study including patients who underwent thyroid surgery for papillary thyroid carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that the incidence of hypocalcemia was reduced with preservation of at least one parathyroid gland with intact blood supply (8). Some scholars have suggested that the functional recovery of superior and inferior parathyroids preserved in situ is different (9). In addition, some scholars have indicated that parathyroid autotransplantation is another effective strategy to preserve parathyroid function (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the incidence of hypocalcemia was reduced with preservation of at least one parathyroid gland with intact blood supply (8). Some scholars have suggested that the functional recovery of superior and inferior parathyroids preserved in situ is different (9). In addition, some scholars have indicated that parathyroid autotransplantation is another effective strategy to preserve parathyroid function (10).…”
Section: Introductionmentioning
confidence: 99%